The Digital Guardian: AI Fall Detection vs. The Limits of Manual Monitoring - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Falls are a significant global health challenge, particularly among the elderly and hospitalized patients, leading to injury, loss of independence, and subst...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Machine Learning